The Importance of Faith: Tax Morale and Religiosity - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2003)
The intention of this paper is to analyze religiosity as a factor that potentially affects tax morale. For this purpose, a multivariate analysis has been done with data from the World Values Survey 1995- 1997, covering more than thirty countries at the individual level. Several variables, such as church attendance, religious education, being an active member of a church or a religious organization, perceived religiosity, religious guidance and trust in the church have been analyzed. The results suggest that religiosity raises tax morale.
Keywords: H26; H73; K42; 330; Tax morale; Tax compliance; Religiosity